ISOLATION OF GERM CELL GOLGI APPARATUS FROM SEMINIFEROUS TUBULES OF RAT TESTES - Cunningham, W. P. (The Rockefeller University Press, 1971)
Intact Golgi apparatus have been isolated with good purity from rat testis by a simplified sucrose gradient technique. The procedure is inherently selective in that most of the Golgi apparatus in the isolate are from germ cells in late spermatocyte or early spermatid development. No Sertoli cell Golgi apparatus are present in the fraction. Biochemical analyses showed that the enzyme N-acetylglucosamine galactosyltransferase is enhanced in the band containing Golgi apparatus. Because they are easy to isolate, and because they are involved with the formation of a specific internal cellular component (the acrosome), these Golgi apparatus will be useful objects for comparison with other kinds of Golgi apparatus and for other studies leading to a better understanding of the basic functioning of Golgi apparatus.